2013
DOI: 10.3329/medtoday.v25i1.16070
|View full text |Cite
|
Sign up to set email alerts
|

Proteinuria in Chronic Kidney Disease and its Management

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…For table (1), the knowledge of both study groups for the risks and side effects of taking nutritional supplements is shown. For control group, the results revealed that 30/30 (100%) was known the risks, whereas there are 0/30 (0%) was unaware the risks.…”
Section: Resultsmentioning
confidence: 99%
“…For table (1), the knowledge of both study groups for the risks and side effects of taking nutritional supplements is shown. For control group, the results revealed that 30/30 (100%) was known the risks, whereas there are 0/30 (0%) was unaware the risks.…”
Section: Resultsmentioning
confidence: 99%
“…According to the 2012 data, the total expenses for medical treatment of patients with end‐stage renal failure is similar to those of all cancer patients, and the expenses of medical treatment per patient are the highest among all diseases . Therefore, in patients with a high potential risk of kidney function, it is essential to periodically monitor the kidney function and to treat the progressive slowing down of the renal function as early as possible . An increased excretion of urinary protein, especially albumin, is an early finding of renal damage, and measurement of urinary albumin has been a useful marker for diagnosis and follow‐up of renal failure with estimated glomerular filtration rate .…”
Section: Introductionmentioning
confidence: 99%
“…The urine albumin/creatinine ratio (ACR) test is also used to screen patients with chronic diseases that put them at an increased risk of developing kidney disease. ACR is a surrogate marker of urine albuminuria . A quantitative evaluation of moderately increased albuminuria requires the use of expensive biochemical instruments and reagents, making it difficult to perform in small or medium‐sized clinics.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations